Peranan Stres Akademik Terhadap Subjective Well-Being dengan Perceived Social Support sebagai Moderator pada Mahasiswa Magang Atau Bekerja - Barirahma Martinasia Islahuddiny; Fransisca Iriani Roesmala Dewi; Meylisa Permata Sari (Fakultas Psikologi Universitas Tarumanagara, 2022)
In this era of rapid growth on technology literacy, students as a bridge between the world of school and work hold great responsibilities and are required to work in a fast-paced environment, more complex than their predecessors. As students who are doing internships or working, they have two responsibilities, namely academic and professional at the same time. This can cause students to experience poor learning patterns due to lack of time management skills and tend to multi-task. Those who have many academic and other demands but are unable to cope with them will experience academic stress. In addition, time management is closely related to the work-life balance phenomenon. This can affect the low subjective well-being. Thus, academic stress can affect the decline of subjective well-being in students who are doing internships or working. This study aims to examine the relationship between academic stress and subjective well-being moderated by perceived social support. Data was collected by distributing questionnaires using the Perceived Academic Stress Scale (PAS), Satisfaction With Life Scale (SWLS), Scale of Positive and Negative Experience (SPANE), and Multidimensional Scale of Perceived Social Support (MSPSS) with 387 participants using linear regression quantitative research design. The result shows that p < 0.05 for regression and p > 0.05 for moderation analysis. Thus, show that there is an influence between academic stress and subjective well-being and social support cannot strengthen the effect of academic stress and subjective well-being.